Ka Band Phase Locked Loop Oscillator Dielectric Resonator Oscillator for Satellite EHF Band Receiver - S. Coco; F. Di Maggio; A. Laudani; I. Pomona (Active and Passive Electronic Components)
This paper describes the design and fabrication of a Ka Band PLL DRO having a fundamental oscillation frequency of 19.250 GHz, used as local oscillator in the low-noise block of a down converter (LNB) for an EHF band receiver. Apposite circuital models have been created to describe the behaviour of the dielectric resonator and of the active component used in the oscillator core. The DRO characterization and measurements have shown very good agreement with simulation results. A good phase noise performance is obtained by using a very high Q dielectric resonator.